EXPLORING THE SOCIETAL AND LEGAL IMPACTS OF CHILD IDENTITY CARD REGULATIONS: LESSONS FROM RECENT IMPLEMENTATION - Hamidah, Nabila Putri; Nazriah, Ainun (Universitas Negeri Gorontalo, 2023)
This study discusses the comparative results of the Indonesia Kid Identity Card (KIA). The research uses a qualitative approach. The techniques for collecting data using interviews, observation, and documentation. The analysis of this study used data reduction, data display, and conclusions. The result shows that there are similarities and differences in that the communication in Pondok Melati District is not effective, meanwhile in South Bekasi District shows that communication is effective. The human resources in Pondok Melati District are not well being performed. There are still several issues with the management in Pondok Melati District, such as the lack of professionalism among the staff, the attitude of the leadership, and a commitment that satisfies the society and meets the expectations of the community. Meanwhile, South Bekasi District can be considered better than compared to Pondok Melati District, in the satisfaction of the community towards the services provided by South Bekasi District. The Bureaucracy structure in both areas is similar, as both follow government regulations. However, there is an obstacle in the implementation of the Indonesia Kid Identity Card (KIA) program due to the lack of awareness regarding ownership of the Indonesia Kid Identity Card (KIA)